There's no such thing as an easy job - Tsumura, Kikuko, 1978- (Bloomsbury Publishing, 2021)
"A young woman walks into an employment agency and requests a job that has the following traits: it is close to her home, and it requires no reading, no writing - and ideally, very little thinking. She is sent to a nondescript office building where she is tasked with watching the hidden-camera feed of an author suspected of storing contraband goods. But observing someone for hours on end can be so inconvenient and tiresome. How will she stay awake? When can she take delivery of her favourite brand of tea? And, perhaps more importantly--how did she find herself in this situation in the first place? As she moves from job to job, writing bus adverts for shops that mysteriously disappear, and composing advice for rice cracker wrappers that generate thousands of devoted followers, it becomes increasingly apparent that she's not searching for the easiest job at all, but something altogether more meaningful..."--